Bibliometrics and Visual Analysis of rTMS in Recent Five Years Based on CiteSpace - Heping ZHENG; Bo ZHANG; Yuxi LI; Dongling ZHONG; Yanping TIAN; Juan LI; Zhong ZHENG; Rongjiang JIN (康复学报)
Objective:To summarize the current research status, hot spots and their evolution trend through bibliometrics and visual analysis of the latest research on repetitive transcranial magnetic stimulation (rTMS) conducted in recent five years at home and abroad.Methods:The related literatures search of rTMS during 2015-2019 were conducted in CNKI and Web of Science (WoS). CiteSpace software was used to analyze the co-occurrence analysis of authors, countries and institutions, and keywords; conduct cluster analysis, time evolution analysis and Burst analysis on keywords, and draw the knowledge map.Results:A total of 996 articles were obtained from CNKI search, of which Zhang Tong, the author who had the most publications; the most published papers were from the School of Rehabilitation Medicine, Capital Medical University. A total of 2, 086 literatures were obtained from WoS search. Jonathan Downar had the most publications. The most published country was the United States, and the high degree of center was Portugal. The research hotspots in the field of rTMS at home and abroad mainly focus on the treatment of mental illness such as depression and schizophrenia, the research on the cognitive sequelae of cerebral apoplexy, the recovery of motor dysfunction, and the exploration of the mechanism of action of each functional area of cerebral cortex. It was predicted that this field would continue to study its influence on brain region function and further reveal its mechanism in the future.Conclusion:CiteSpace software was used to visually analyze the research literature of rTMS in recent five years at home and abroad, which directly reflected the current research status, hot spots and their evolution trend of rTMS. It provided some references for the topic selection and future direction of rTMS research.